Process capability study in electronic industry- case study on aircoil lead frame welding (HM72B-06XXX) - Noor Hidayatul Adawiyah, Shahizan (2013)
The aim of this project is to implement the industrial engineering tools in selected manufacturing company to identify the process capability at the company production lines and to improve the quality of the product of company. The chosen company is B.I Technology Sdn. Bhd. and the product being analyzed is molded inductor. The capability data were obtained from B.I Technology and further analysis on the data was done manually and by using MINITAB software. The process of understanding the control and the capability (PUCC) is an iterative closed loop process for continuous improvement. It covers the DMAIC toolkit in the three phases. PUCC is an iterative approach that rotates between the three pillars of the process of understanding, process control, and process capability. The objective of the six sigma study of Molded Inductance is to achieve perfection molded manufacturing by reviewing the present robust manufacturing process, to find out way to improve and modify the process, which will yield molded inductance that are defect free and will give more customer satisfaction. The application of six sigma led to an improved process capability. At the end of this project the result is the Cpk had being improved from 0.84 to 1.75.